1989
DOI: 10.1007/bf00048301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of cytochrome photooxidation and conformational dynamics of Chromatium reaction center complexes

Abstract: A temperature dependence of multiheme cytochrome c oxidation induced by a laser pulse was studied in photosynthetic reaction center preparations from Chromatium minutissimum. Absorbance changes and kinetic characteristics of the reaction were measured under redox conditions where one or all of the hemes of the cytochrome subunit are chemically reduced (E h =+300 mV or E h =-20 to -60 mV respectively). In the first case photooxidation is inhibited at temperatures lower than 190-200 K with the rate constant of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…First, electron transfer to P+ is faster from heme c-552 than from heme c-559, as mentioned above: this difference does not agree with the proposed arrangement unless c-559 acts as an intermediate in the oxidation of c-552, a property that has not yet been evidenced. Second, according to the classical data of several laboratories obtained on a number of bacterial species, one low-potential heme remains fully photooxidizable at low temperatures (Vredenberg & Duysens, 1964;De Vault & Chance, 1966;De Vault et al, 1967; ; ; Dutton et al, 1970Dutton et al, , 1971; Dutton, 1971;Tiede et al, 1976; Nitschke & Rutherford, 1989) whereas á major part of the high-potential hemes is no longer capable of efficient electron donation to P+ (Vredenberg & Duysens, 1964;Dutton et al, 1970Dutton et al, , 1971Dutton, 1971;Rubin et al, 1989; Nitschke & Rutherford, 1989). This fact has long served as an argument for the concept of independent and parallel pathways for lowand high-potential heme oxidation by P+, a concept which could also account for room temperature results showing that a faster electron donation from low-potential hemes than from high-potential hemes takes place in many bacterial species Seibert & De Vault, 1970;Kononenko et al, 1974;Tiede et al, 1976; Dutton & Prince, 1978; Bixon & Jortner, 1986a,b, 1989.…”
mentioning
confidence: 99%
“…First, electron transfer to P+ is faster from heme c-552 than from heme c-559, as mentioned above: this difference does not agree with the proposed arrangement unless c-559 acts as an intermediate in the oxidation of c-552, a property that has not yet been evidenced. Second, according to the classical data of several laboratories obtained on a number of bacterial species, one low-potential heme remains fully photooxidizable at low temperatures (Vredenberg & Duysens, 1964;De Vault & Chance, 1966;De Vault et al, 1967; ; ; Dutton et al, 1970Dutton et al, , 1971; Dutton, 1971;Tiede et al, 1976; Nitschke & Rutherford, 1989) whereas á major part of the high-potential hemes is no longer capable of efficient electron donation to P+ (Vredenberg & Duysens, 1964;Dutton et al, 1970Dutton et al, , 1971Dutton, 1971;Rubin et al, 1989; Nitschke & Rutherford, 1989). This fact has long served as an argument for the concept of independent and parallel pathways for lowand high-potential heme oxidation by P+, a concept which could also account for room temperature results showing that a faster electron donation from low-potential hemes than from high-potential hemes takes place in many bacterial species Seibert & De Vault, 1970;Kononenko et al, 1974;Tiede et al, 1976; Dutton & Prince, 1978; Bixon & Jortner, 1986a,b, 1989.…”
mentioning
confidence: 99%
“…It is well known that both high‐potential and low‐potential cytochromes act as secondary electron donors to the photooxidized special pair of RC cytochromes and are intermediates of cyclic electron transport, whereas low‐potential hemes connect RC to a terminal electron donor (substrate of oxidation). We studied the kinetics of the dark reduction of P + under the redox conditions with only high‐potential hemes ( E h =200–300 bacteriochlorophylls (P + ) [1, 3, 4, 9, 11, 12]; the high‐potential mV), both high‐potential and mid‐potential hemes ( E h =50–150 mV), or the three pairs of hemes ( E h from −20 to −60 mV) poised in a chemically reduced state (therefore, capable of donating an electron to P + ). It was found that the rate of the photoinduced electron transfer from high‐potential hemes to P + , measured at E h =200–300 mV, coincides with the reaction rate measured earlier in chromatophores and whole cells of this species of photosynthetic bacteria [9].…”
Section: Resultsmentioning
confidence: 99%
“…We studied the kinetics of the dark reduction of P + under the redox conditions with only high‐potential hemes ( E h =200–300 bacteriochlorophylls (P + ) [1, 3, 4, 9, 11, 12]; the high‐potential mV), both high‐potential and mid‐potential hemes ( E h =50–150 mV), or the three pairs of hemes ( E h from −20 to −60 mV) poised in a chemically reduced state (therefore, capable of donating an electron to P + ). It was found that the rate of the photoinduced electron transfer from high‐potential hemes to P + , measured at E h =200–300 mV, coincides with the reaction rate measured earlier in chromatophores and whole cells of this species of photosynthetic bacteria [9]. Similar coincidence was observed under redox conditions when the three pairs of cytochrome hemes were chemically reduced ( E h from −20 to −60 mV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation